Relación entre el trabajo remoto y la productividad de los trabajadores del Ministerio Público de Loreto periodo 2020 – 2022 - Marill Tello, Gabriela Beatriz (2023)
In the context of the COVID19 pandemic, remote work has proven to be an important tool to ensure the operational continuity of private companies and public institutions in Peru, and under normal circumstances, its benefits include reduced travel time, which it allows employees to focus on their tasks, away from the distractions of the office and the opportunity to achieve a better work-life balance. In this sense, the objective of this work is to determine the relationship between remote work and the productivity of the workers of the Public Ministry of Loreto in a pandemic, during the period 2020 - 2022. For this, a quantitative investigation was carried out, of non-experimental nature and correlational design, in which it was found that there is a positive relationship of 80%, between remote work and labor productivity, if it is implemented in an ideal way.